PENGAMBILAN KEPUTUSAN DAN KEPUASAN KONSUMEN DALAM PEMBELIAN BUCKET BUNGA SEGAR DI ROSE FLORIST BANDAR LAMPUNG - Dwi Nadya Lestari Fatma; Wuryaningsih Dwi Sayekti; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
This study aims to determine decision making, purchasing patterns, and customer satisfaction of fresh flower buckets. The research was conducted at Rose Florist Bandar Lampung using a survey method.with the total samples of 40 customers. The samples were determined using Accidental Sampling. Data collection was carried out in November 2019 - February 2020. Decision making and purchasing patterns were analyzed using qualitative descriptive method and the level of customer satisfaction was analyzed using the Satisfaction Customer Index (CSI) and Importance Performance Analysis (IPA). The results showed that the decision making in purchasing fresh flower buckets was mostly influenced by friends and the attribute that was considered was the appearance of the product. The highest number of purchased buckets of fresh flowers.in the last three months was as many as 4 buckets, the frequency of buying was 3-4 times, and type mostly bought was the small bucket. Most the consumers of the fresh flower bucket were satisfied.  Based on the Cartesian IPA diagram, the attribute in quadrant I is price. The attributes in quadrant II are product appearance and freshness of flowers. Attributes in quadrant III are attributes of speed of assembly and ease of obtaining. And, the attributes in quadrant IV are service and the diversity of the flower types.Key words: customer satisfaction, decision making, fresh flower bucket, purchasing patterns.